النسخ الدلالي عند الحنفية: دراسة نقدية أصولية - السلمي، إبراهيم بن صمايل بن صويمل (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2023)
النسخ أحد الموضوعات الرئيسة في علم أصول الفقه، وتنبع أهميته من ارتباطه بالقرآن الكريم والسنة والنبوية، كما أن من شروط الاجتهاد والفتيا أن يكون المجتهد والمفتي على علم بالناسخ والمنسوخ؛ لأنه لو لم يعلم ذلك لأفتى بالحكم المنسوخ وعمل به، وهذا باطل. ولا يخالف أحد من المسلمين في وقوع النسخ في نصوص الكتاب والسنة؛ فقد ظهر وقوعه في نصوص شرعية محكمة، وقد قال الله تعالى: ((مَا نَنْسَخْ مِنْ آَيَةٍ أَوْ نُنْسِهَا نَأْتِ بِخَيْرٍ مِنْهَا أَوْ مِثْلِهَا)). ومن المتقرر أن طريق ثبوت النسخ يجب أن يكون بنص من القرآن الكريم أو السنة النبوية؛ فإن بقاء النص الشرعي وحكمه أو رفعهما بالنسخ يترتب عليه بقاء الحكم الشرعي الذي دل عليه النص أو إلغاؤه، فالقول بنسخ نص أو عدم نسخه لا بد فيه من الحذر، بحيث لا يكون ادعاء النسخ إلا بنص ثابت. لكن حصل لدى الحنفية توسع في النسخ باحتمالات تدلهم عليه، فجاء البحث كاشفا عن مفهوم النسخ الدلالي عند الحنفية، بذكر مواطنه، وأثره، مع الرد عليهم. Abrogation is one of the main topics in the science of jurisprudence, and its importance stems from its connection with the Holy Qur’an, the Sunnah, and the Prophet. One of the conditions for ijtihad and fatwa is that the diligent person and the mufti must be aware of the abrogated and abrogated; Because if he had not known that, he would have issued a fatwa with the abrogated ruling and acted upon it, and this is invalid. No Muslim disagrees with the occurrence of abrogation in the texts of the Qur’an and Sunnah. Its occurrence has been shown in authoritative legal texts, and God Almighty said: ((We do not abrogate a verse or cause it to be forgotten. We bring back something better than it or similar to it.)) It is decided that the way to prove abrogation must be through a text from the Holy Qur’an or the Sunnah of the Prophet. The survival of the legal text and its ruling, or their removal by abrogation, results in the survival or cancellation of the legal ruling indicated by the text. So, saying that a text was abrogated or not abrogated requires caution, such that the claim of abrogation can only be made with an established text. But among the Hanafis there was an expansion in abrogation with possibilities that would guide them to it, so the research revealed the semantic concept of abrogation according to the Hanafis, by mentioning its origins and its impact, with a response to them.
Keywords: المذهب الحنفي -- الفقه الإسلامي -- الحكم المنسوخ -- أصول الفقه -- الأحكام الشرعية